Диференційна діагностика високорослості у дітей - Зелінська, Н. Б.; Малашонок, В. Б. (Clinical Endocrinology and Endocrine Surgery, 2009)
Different diseases with high growth syndrome in children are shown: family high growth syndrome, diffuse toxic goiter, hypothalamo-hypophyseal subgigantism, Marfan's and Beckwith-Wiedemann's syndromes, precocious puberty. All patients have common sign — tall height. Diagnostic routine methods included: total hormonal stature evaluation with somathotropin and thyreoid function determination and other specialists consultations.